Prestressed duct grouting material and preparation method thereof
Patent Information
- Application Number
- CN202611210129.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-08-11
AI Technical Summary
该技术虽通过工业废渣的火山灰活性效应优化孔道填充密实度,但其膨胀性能依赖传统膨胀剂(添加比例为0-5份),未能解决氧化钙类膨胀剂早期水化速率过快导致的流动度经时损失问题;在抗氯离子侵蚀方面,该方案仍以水泥水化产物的物理屏障作用为主,缺乏主动吸附氯离子的功能设计;且该体系中额外引入了消泡剂、保水剂等多种外加剂,组分间相互作用复杂,影响浆体稳定性控制
1、采用硅基水滑石材料,利用纳米二氧化硅表面固定的磺酸根与高效萘系减水剂的静电协同分散,配合层状双金属氢氧化物壳层的硝酸根-氯离子离子交换机制,解决了现有压浆料缺乏主动抗氯离子侵蚀能力的问题,实现了氯离子吸附率≥20%,显著延长预应力结构在氯盐环境下的服役寿命。
Smart Images

Figure CN122705246B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, and in particular to a prestressed duct grouting material and its preparation method. Background Technology
[0002] Grouting of prestressed concrete ducts is a crucial step in the construction of prestressed concrete structures. The grout fills the space between the prestressing tendons and the duct walls, protecting the tendons from corrosion and ensuring the tendons and structure work together to bear stress. As bridge engineering in my country develops towards longer spans and higher durability, the performance requirements for prestressed concrete duct grout are increasingly stringent. The current industry standard JTG / T 3650-2020 explicitly requires that grout possess comprehensive properties such as high fluidity, minimal fluidity loss over time, zero bleeding, micro-expansion, and high resistance to chloride ion penetration.
[0003] Currently, prestressed grouting materials used in China and abroad are mainly formulated with ordinary silicate cement and admixtures such as expanding agents and water-reducing agents. To address the problem of insufficient duct filling caused by the hardening shrinkage of cement paste, existing technologies typically add calcium oxide or calcium sulfoaluminate expanding agents, utilizing their volume expansion during hydration to compensate for shrinkage. However, traditional calcium oxide expanding agents undergo rapid hydration, releasing significant heat and expanding even during the plastic stage of the paste, leading to a rapid decrease in fluidity and increased bleeding rate. Furthermore, early expansion cannot effectively compensate for later shrinkage, especially at low temperatures where the cement hydration rate slows down, exacerbating the mismatch between premature calcium oxide expansion and cement setting. In addition, existing grouting systems rely primarily on the physical barrier effect of cement hydration products for chloride ion corrosion protection, lacking the ability to actively adsorb externally penetrating chloride ions, making it difficult to meet the durability requirements of bridges exceeding 100 years. While polycarboxylate superplasticizers offer excellent water reduction, their carboxyl functional groups readily react with calcium ions released during calcium oxide hydration, rendering them ineffective and resulting in poor fluidity retention. For example, CN113061002A discloses a high-durability, micro-expansion, green prestressed grouting material, which uses a mixture of ceramic waste and steel slag to improve resistance to chloride ion erosion and durability while reducing production costs. Although this technology optimizes the pore filling density through the pozzolanic activity of industrial waste, its expansion performance relies on traditional expansion agents (added at a ratio of 0-5 parts), failing to address the issue of fluidity loss over time caused by the excessively rapid early hydration rate of calcium oxide-based expansion agents. In terms of resistance to chloride ion erosion, this solution still relies mainly on the physical barrier effect of cement hydration products, lacking a functional design for actively adsorbing chloride ions. Furthermore, the system introduces multiple admixtures such as defoamers and water-retaining agents, resulting in complex interactions between components and affecting the stability control of the grout.
[0004] Therefore, developing a prestressed grouting material that combines high fluidity, zero bleeding, delayed micro-expansion, active resistance to chloride ion erosion, good component compatibility, few types of admixtures, and excellent low-temperature adaptability has significant engineering application value. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a prestressed duct grouting material and its preparation method.
[0006] The technical solutions provided by the embodiments of the present invention are as follows: A prestressed duct grouting material and its preparation method, comprising the following steps: S1. Preparation of multifunctional nano-silica: S101. Disperse pre-dried nano-silica with 1.5%-3.5% of 3-(trihydroxysilyl)propanesulfonic acid by mass of nano-silica in an ethanol aqueous solution with a mass ratio of 1:1. Reflux at 70-80℃, and obtain sulfonated nano-silica by centrifugation, washing and drying. In the above process, the three hydroxyl groups in the 3-(trihydroxysilyl)propanesulfonic acid molecule form a silanol reactive intermediate in the presence of water. Subsequently, it undergoes a dehydration condensation reaction with the silanol groups on the surface of nano-silica to generate a stable siloxane covalent bond (Si-O-Si-), thereby grafting the sulfonic acid group (-SO3H) onto the surface of nano-silica. The specific reaction formula is as follows: Through this covalent grafting, the sulfonic acid groups are firmly anchored to the surface of nano-silica, giving it strong negative charge (significantly reduced zeta potential), which enables the nanoparticles to maintain good dispersion stability in the high ionic strength environment of cement paste and to be less prone to agglomeration. When this sulfonated nano-silica is used in grouting, its surface negative charge generates a synergistic electrostatic repulsion with the sulfonate groups of the highly efficient naphthalene-based water-reducing agent in the admixture, further optimizing the dispersion effect of cement particles. This reduces grout viscosity, increases initial fluidity, and minimizes fluidity loss over time. Simultaneously, the strong hydrophilicity of the sulfonate group and its counterion (Na+) further enhance its properties. + or Ca 2+ Hydration helps bind free water, which plays a positive role in achieving the goal of zero water leakage; S102. The sulfonated nano-silica obtained in step S101 is dispersed in a mixed solution containing calcium salt, magnesium salt and aluminum salt, the pH is adjusted to 10-11, and a co-precipitation reaction is carried out at 60-80℃ for 6-12 hours to allow calcium magnesium aluminum layered bimetallic hydroxide nanosheets to grow in situ on the surface of nano-silica. After centrifugation, washing and drying, silicon-based hydrotalcite material is obtained. In step S2 above, sulfonated nano-silica is dispersed in a mixed solution containing calcium nitrate, magnesium nitrate, and aluminum nitrate, wherein the molar ratio of calcium, magnesium, and aluminum is 2-4:1:1. Sodium hydroxide solution is added dropwise under vigorous stirring to adjust the pH to 10-11, creating a strongly alkaline environment. Simultaneously, the temperature is raised to 60-80℃ and maintained for 6-12 hours. During this process, OH... - With Ca in solution 2+ Mg 2+ Al 3+ A coprecipitation reaction occurs, generating positively charged layered bimetallic hydroxide (LDH) crystal nuclei. During pH adjustment, the sulfonic acid groups on the surface of the nano-silica transform into negatively charged sulfonate ions (-SO32-). - The strong electrostatic attraction between the LDH crystal nucleus and the positively charged LDH crystal nucleus drives the selective heterogeneous nucleation and in-situ growth of the LDH crystal nucleus on the surface of nano-silica, ultimately forming a core-shell structure of nano-silica loaded with hydrotalcite. The specific reaction formula is as follows: 2Ca(NO3)2+Mg(NO3)2+Al(NO3)3+6NaOH→[Ca2MgAl(OH)6] + NO3 - +6NaNO3 Chloride ions are the primary factor leading to corrosion failure of prestressed tendons in prestressed concrete structures. When chloride ions penetrate the surface of prestressed tendons, they destroy the dense passivation film on the surface, triggering a localized electrochemical corrosion reaction. The resulting rust products can expand in volume to 2 to 6 times the original steel reinforcement volume, leading to cracking and spalling of the concrete cover. This severely reduces the load-bearing capacity and durability of the structure. Especially in the concealed project of prestressed ducts, once chloride ions penetrate through the pores or cracks of the grouting material itself, the corrosion process is difficult to detect and repair in time, which may cause sudden structural damage and major safety accidents. To address the aforementioned chloride ion hazards, this solution introduces silicon-based hydrotalcite (LDH) material into the grouting material. Through the steps described above, a calcium-magnesium-aluminum layered bimetallic hydroxide shell is grown in situ on the surface of nano-silica. The sulfonate ions covalently fixed on the surface of the nano-silica core provide a negatively charged dispersion effect, synergistically optimizing the dispersion of cement particles with a highly efficient naphthalene-based water-reducing agent, ensuring high fluidity and low bleeding of the grout. The LDH shell, on the other hand, functions as a chloride ion capturing unit. The LDH interlayer is rich in exchangeable nitrate ions. When chloride ions permeate from the external environment into the pore solution of the grout, the nitrate ions in the LDH interlayer undergo an ion exchange reaction with the chloride ions, firmly capturing and fixing the chloride ions in the LDH interlayer. At the same time, nitrate ions that are harmless to the cement matrix and steel reinforcement are released. This process not only effectively reduces the concentration of free chloride ions in the pores and blocks the migration path of chloride ions to the surface of the prestressing tendons, but also refines the pore structure of the cement stone through the filling effect of the nano silica core and the physical barrier effect of the LDH shell, significantly improving the grout's resistance to chloride ion penetration. Through the above dual mechanism of active adsorption and passive barrier, the core-shell structure of nano silica loaded with hydrotalcite can effectively delay the corrosion process of the prestressing tendons and increase the chloride ion adsorption rate to more than 20%, thereby greatly extending the service life of prestressed concrete structures in chloride salt environments. S2. Preparation of pre-dispersion: Weigh water according to the ratio, add silicon-based hydrotalcite material and polyethylene glycol to water, and ultrasonically disperse at 300-500W ultrasonic power and 40-50kHz frequency for 10-20 minutes to obtain a pre-dispersion. The core mechanism of this process lies in utilizing the cavitation effect generated by ultrasound in liquids. Ultrasound generates alternating pressure waves of varying density in water through high-frequency vibrations. When the sound pressure amplitude exceeds the hydrostatic pressure of the liquid, tiny vacuum bubble nuclei are formed in the water. These bubble nuclei rapidly expand and undergo implosive collapse in subsequent sound pressure cycles, instantly generating a high-temperature and high-pressure environment of thousands of degrees Celsius and tens of megapascals in the local area. At the same time, it releases strong shock waves and microjets. This extreme physical energy can effectively redisperse the softly aggregated particles in silicon-based hydrotalcite materials due to electrostatic interactions or hydrogen bonds, destroying the secondary aggregation structure between nanoparticles. Meanwhile, as a nonionic surfactant, polyethylene glycol molecules form hydrogen bonds with water molecules through the ether oxygen atoms in their long chains. This adsorption on the surface of nanoparticles creates a hydration film, generating a steric hindrance effect that prevents the particles, which have just been dispersed by ultrasound, from re-aggregating. The synergistic effect of the ultrasonic cavitation effect and the steric hindrance effect of polyethylene glycol enables the silicon-based hydrotalcite material to achieve uniform and stable suspension at the single-particle level in water, forming a uniform and stable pre-dispersion liquid. This pre-dispersion treatment ensures that the silicon-based hydrotalcite material can be uniformly distributed throughout the grouting system when mixed with dry powder, avoiding the failure of chloride ion adsorption function or the decrease in slurry fluidity due to local agglomeration of nanoparticles. This lays a key foundation for achieving high fluidity, zero bleeding, and high chloride ion adsorption efficiency in the grouting material. S3. Preparation of dry powder mixture: Weigh out ordinary silicate cement, rapid-hardening sulfoaluminate cement, anhydrous gypsum, silane-modified calcium oxide, and additives according to the proportions, put them into a dry powder mixer, and stir and mix them at a speed of 20-30 rpm for 10-15 minutes to obtain a dry powder mixture. In the above dry powder mixing process, the shear force and convection mixing effect generated by low-speed mechanical stirring are mainly used to achieve a uniform distribution of each component powder in the mixer on a macro scale. Ordinary silicate cement and rapid hardening sulfoaluminate cement are the main cementing materials. The particle size distribution of the two is similar. Low-speed stirring can avoid dust or particle breakage caused by excessive speed. The addition of anhydrous gypsum during the mixing process allows it to be evenly dispersed between cement particles by mechanical force. Its high specific surface area helps to ensure full contact with cement particles during subsequent hydration, thereby controlling the formation rate and morphology of ettringite. Because of the hydrophobic silane coating on its surface, silane-modified calcium oxide is prone to agglomeration with other hydrophilic powders when directly mixed. However, through gentle stirring at low speed for a long time, the physical grinding and carrying effect of cement and gypsum powder can be used to make a layer of hydrophilic fine powder uniformly adhere to the surface of the silane-modified calcium oxide particles, forming a "hydrophilic shell", thereby improving its fluidity in the dry powder state and its dispersibility during subsequent hydration. The high-efficiency naphthalene-based water-reducing agent in the admixture is in powder form, and sodium citrate is also a crystalline powder. Under low-speed stirring, the two are uniformly attached to the surface of cement particles, avoiding uneven distribution of water-reducing agent or inconsistent retarding effect caused by excessive local concentration. The entire low-speed stirring process, without destroying the original particle size of the powder, relies on the relative movement and position exchange between particles to achieve a macroscopically uniform mixing state of each component. This provides an important guarantee for the simultaneous and uniform participation of each component in the hydration reaction and dispersion process during subsequent water addition and slurry preparation. S4. Preparation of grouting material: Pour the pre-dispersed liquid into a planetary high-speed pulper. With the stirring blade linear speed ≥10m / s, stir at a low speed of 300-500rpm while slowly adding the dry powder mixture. The addition time should be controlled within 30-60s. After all the dry powder has been added, increase the stirring speed to 1200-1500rpm and stir at high speed for 2-3 minutes. Then reduce the stirring speed to 400-600rpm and let it stand for 5-10 minutes. Finally, stir at 800-1000rpm for 30-60s to obtain the prestressed duct grout. The above process can be divided into the following four stages based on the stirring speed: Phase 1: Low-speed feeding and initial wetting (300-500 rpm, feeding time 30-60 seconds): During this stage, the planetary mixing machine operates at a low speed of 300-500 rpm, with a stirring blade linear velocity ≥10 m / s. The operator slowly adds the dry powder mixture to the pre-dispersion liquid over 30-60 seconds. The main purpose of low-speed stirring is to ensure sufficient contact between the dry powder and the liquid without causing violent splashing. When the dry powder comes into contact with the pre-dispersion liquid, the soluble alkali metal sulfates (K2SO4, Na2SO4) on the surface of the cement particles dissolve rapidly, releasing K... + Na + and SO4 2- The hydrolysis of these salts raises the pH of the slurry to 11-12; Simultaneously, tricalcium aluminate (C3A) reacts with anhydrous gypsum (CaSO4) and water added to the formula to form ettringite (3CaO·Al2O3·3CaSO4·32H2O, AFt): C3A + 3CaSO4 + 32H2O → AFt In this reaction, C3A itself provides calcium and aluminum ions, and gypsum provides sulfate ions. The three combine to form needle-like ettringite crystals. The silicon-based hydrotalcite material and polyethylene glycol, which are uniformly suspended in the pre-dispersion liquid, are carried into the gaps between cement particles under stirring. The sulfonate anions of the high-efficiency naphthalene-based water-reducing agent are rapidly adsorbed onto the positively charged areas on the surface of cement particles. The electrostatic repulsion disperses the agglomerated cement particles, preventing the slurry from thickening due to the early structure formed by local hydration. The control of the feeding speed at this stage is crucial. If it is too slow, the early hydration products may overlap prematurely. If it is too fast, it is easy to form "fish-eye" shaped undispersed dry powder clumps. Second stage: High-speed dispersion and homogenization (1200-1500 rpm, 2-3 min): After all the dry powder is added, the stirring speed is increased to 1200-1500 rpm for high-speed stirring. The high shear force input puts the slurry in a strong turbulent state, which can effectively break up the soft agglomerates that may remain in the first stage. The micro-nano particles such as silicon-based hydrotalcite material, silane-modified calcium oxide, and anhydrous gypsum are evenly dispersed into various micro-regions of the cement slurry. The mechanical energy generated by high-speed stirring shears and peels off the hydration products on the surface of cement particles, exposing fresh surfaces for further adsorption by the water-reducing agent, thereby maintaining good fluidity. At the same time, the air bubbles inside the slurry are refined and partially discharged under high shear. The nano-SiO2 cores in the silicon-based hydrotalcite material generate synergistic electrostatic repulsion with the high-efficiency naphthalene-based water-reducing agent through the sulfonate groups fixed on their surface, further optimizing the dispersion effect. At the end of this stage, the slurry reaches a stable suspension state with macroscopic uniformity, consistent color, and no visible agglomerates. Third stage: Static aging (400-600 rpm, 5-10 min): After high-speed stirring, the speed is reduced to 400-600 rpm for static aging. During this time, the slurry transitions from a strongly turbulent state to a weakly convective state, and the system gains a brief period of "structural relaxation." During this process, the following key changes occur: Firstly, tricalcium silicate (the main mineral component of ordinary silicate cement, C3S), which has already begun to hydrate during the high-speed mixing stage, continues to react at this stage. The calcium silicate hydrated colloidal particles that fall off its surface and the colloidal crystal embryos precipitated from supersaturated ions in the solution together constitute the initial calcium silicate hydrated colloidal nucleation sites. These sites are orderly distributed on the surface of cement particles and around the silicon-based hydrotalcite material. Secondly, the hydrophobic coating on the surface of silane-modified calcium oxide remains intact at this stage, and the calcium oxide has not yet come into contact with water, ensuring a delayed expansion window of 2-4 hours. Third, the residual microbubbles introduced by high-speed stirring inside the slurry float to the surface and are discharged under low shear conditions. The sulfonate groups fixed on the surface of the nano-SiO2 core in the silicon-based hydrotalcite material work synergistically with the high-efficiency naphthalene-based water-reducing agent to reduce the surface tension of the bubbles and assist in defoaming. Fourth, polyethylene glycol molecules bind with free water through hydrogen bonds, forming a stable hydration film on the surface of nanoparticles and cement particles. The steric hindrance effect effectively prevents the particles from re-aggregating, providing a structural basis for zero bleeding in the slurry. Fourth stage: Final homogenization (800-1000 rpm, 30-60 s): After aging, the grout is stirred again at 800-1000 rpm for 30-60 seconds. This short-term high-speed stirring reactivates the flow dynamics of the slurry, breaks up the weak structural network caused by weak flocculation or initial hydration during aging, and restores the slurry to a uniform and fluid pouring state. After the final stirring, the distribution of silicon-based hydrotalcite material in the slurry is more uniform, and the chloride ion adsorption functional units are fully exposed. Silane-modified calcium oxide is uniformly suspended in the slurry, preparing for the delayed expansion in the following 2-4 hours. The synergistic effect of the high-efficiency naphthalene-based water-reducing agent and sodium citrate keeps the fluidity loss over time within the specified range. At this time, the grout has a uniform appearance, no bleeding, no visible bubbles, and the initial fluidity is stable at 14-18 seconds, which can be used immediately for prestressed duct grouting construction.
[0007] Preferably, the number average molecular weight of polyethylene glycol is 1000-3000 Da.
[0008] Preferably, the admixture is a compound of a high-efficiency naphthalene-based water-reducing agent and sodium citrate in a mass ratio of 20-40:1.
[0009] Preferably, the silicon-based hydrotalcite material is a calcium magnesium aluminum layered bimetallic hydroxide@nano silica core-shell material, wherein the nano silica is the core, and the calcium magnesium aluminum layered bimetallic hydroxide nanosheets are grown in situ on the surface of the nano silica to form a shell layer, which has the function of chloride ion adsorption, with a chloride ion adsorption rate ≥20%.
[0010] Preferably, the specific surface area of anhydrous gypsum is 300-500 m² / g. 2 / kg.
[0011] Preferably, silane-modified calcium oxide is prepared by the following steps: Octyltriethoxysilane or dodecyltrimethoxysilane is pre-hydrolyzed and then sprayed into calcium oxide powder. The mixture is stirred at 80°C for 30 minutes and dried to obtain silane-modified calcium oxide. The amount of silane used is 2%-5% of the mass of calcium oxide. This modified calcium oxide is stable in dry powder form, and after adding water, it begins to hydrate and release heat within 2-4 hours, with a total expansion rate of 0.02%-0.05%. Octyltriethoxysilane or dodecyltrimethoxysilane are chemically grafted onto the surface of calcium oxide to form a dense hydrophobic alkyl chain layer. Although the modified calcium oxide surface is hydrophobic, during the dry powder mixing stage, when it is mixed with hydrophilic fine powder materials such as ordinary silicate cement, rapid-hardening sulfoaluminate cement, and anhydrous gypsum at low speed, the fine powder particles will mechanically adhere to the surface of the hydrophobic calcium oxide particles, forming a "shell". This shell allows the modified calcium oxide to be wetted by water and evenly dispersed in the slurry when water is added, preventing it from floating and agglomerating due to hydrophobicity. The core function of this silane-modified calcium oxide is to provide delayed micro-expansion: in the initial 2-4 hours after adding water, the hydrophobic alkyl layer effectively prevents water molecules from contacting the calcium oxide surface. The grout remains plastic and does not expand. As the cement hydration temperature rises and the alkaline environment gradually destroys the silane layer, calcium oxide begins to hydrate to form calcium hydroxide, resulting in a stable volume expansion of about 0.02%-0.05%. This compensates for the chemical shrinkage and drying shrinkage in the later stages of cement hydration, preventing voids or cracks in the grout due to shrinkage. This ensures tight filling and long-term durability between the prestressing tendons and the duct walls. In addition, the heat released during the calcium oxide hydration process can increase the internal temperature of the grout. Especially in low-temperature environments (such as 5-10℃), this local temperature rise can accelerate the cement hydration reaction rate, shorten the grout setting time, reduce the slow early strength development and frost damage risk caused by low temperature, and effectively expand the low-temperature construction window of the grout.
[0012] Preferably, the high-speed pulper is a planetary high-speed pulper with a stirring blade linear velocity ≥10m / s.
[0013] Preferably, the performance indicators of the grout are: initial fluidity 14-18s, 30min fluidity ≤22s, 3h bleeding rate 0%, 3h free expansion rate 0-2%, 7d compressive strength ≥50MPa, and 28d compressive strength ≥60MPa.
[0014] Compared with the prior art, the beneficial effects of the present invention are: 1. Using silicon-based hydrotalcite material, the electrostatic synergistic dispersion of sulfonate ions fixed on the surface of nano-silica and high-efficiency naphthalene-based water-reducing agent, combined with the nitrate-chloride ion exchange mechanism of the layered bimetallic hydroxide shell, solves the problem of the lack of active resistance to chloride ion erosion in existing grouting materials, achieving a chloride ion adsorption rate of ≥20%, and significantly extending the service life of prestressed structures in chloride salt environments.
[0015] 2. Silane-modified calcium oxide is used, and the hydrophobic alkyl chains grafted by chemical grafting achieve a 2-4 hour delayed hydration heat release. This meets the shrinkage compensation requirements in the later stage of cement hydration, solving the problem of premature expansion in the plastic stage of traditional calcium oxide expansive agents, which leads to decreased fluidity and increased bleeding. At the same time, the heat release of hydration is used to increase the internal temperature of the slurry, achieving construction adaptability in low-temperature environments (5-10℃). The total expansion rate is controlled at 0.02%-0.05%, ensuring dense filling of the pores.
[0016] 3. By employing the synergistic effect of sulfonated nano-silica, high-efficiency naphthalene-based water-reducing agent, polyethylene glycol, and silicon-based hydrotalcite materials, a multi-dispersion stabilization mechanism is formed through electrostatic repulsion, steric hindrance, and hydration film. This solves the problem of poor compatibility caused by the need to add multiple admixtures (defoamers, thickeners, etc.) to traditional grouting materials. It achieves high-performance indicators such as initial flowability of 14-18s, 30min flowability ≤22s, and 3h bleeding rate of 0%, meeting the stringent requirements for prestressed duct construction. Attached Figure Description
[0017] Figure 1 The figures show the water-bearing performance data of the embodiments and comparative examples of the present invention; Figure 2 This is a physical image of the standard curing test block of the grouting material prepared in Example 3 of the present invention. Detailed Implementation
[0018] The technical solutions of this invention are described below. It should also be noted that, to make the embodiments more detailed, the following embodiments are the best and preferred embodiments; those skilled in the art can also use other alternative methods to implement some well-known technologies.
[0019] Example 1: Preparation of prestressed duct grouting material: The prestressed duct grouting material comprises the following components in parts by weight:
[0020] S1. Preparation of multifunctional nano-silica: S101. Pre-dried nano-silica and 2.5% by mass of 3-(trihydroxysilyl)propanesulfonic acid are dispersed in an ethanol aqueous solution with a mass ratio of 1:1. The mixture is refluxed at 75°C, and after centrifugation, washing and drying, sulfonated nano-silica is obtained. S102. The sulfonated nano-silica obtained in step S101 is dispersed in a mixed solution containing calcium salt, magnesium salt and aluminum salt, the pH is adjusted to 10-11, and a co-precipitation reaction is carried out at 70℃ for 9 h to allow calcium magnesium aluminum layered bimetallic hydroxide nanosheets to grow in situ on the surface of nano-silica. After centrifugation, washing and drying, silicon-based hydrotalcite material is obtained. S2. Preparation of the pre-dispersion: Weigh water according to the ratio, add silicon-based hydrotalcite material and polyethylene glycol to water, and ultrasonically disperse at 400W ultrasonic power and 45kHz frequency for 15 minutes to obtain a pre-dispersion. S3. Preparation of dry powder mixture: Weigh out ordinary silicate cement, rapid-hardening sulfoaluminate cement, anhydrous gypsum, silane-modified calcium oxide, and additives according to the proportions, put them into a dry powder mixer, and stir and mix them at 25 rpm for 10 minutes to obtain a dry powder mixture. S4. Preparation of grouting material: Pour the pre-dispersed liquid into a planetary high-speed pulper with a stirring blade linear velocity ≥10m / s and stir at a low speed of 400rpm. While stirring, slowly add the dry powder mixture, and complete the addition within 45s. After all the dry powder has been added, increase the stirring speed to 1300rpm and stir at high speed for 2min. Then reduce the stirring speed to 500rpm and let it stand for 10min. Finally, stir at 900rpm for 45s to obtain the prestressed duct grout.
[0021] Example 2: Preparation of prestressed duct grouting material: The prestressed duct grouting material comprises the following components in parts by weight:
[0022] S1. Preparation of multifunctional nano-silica: S101. Pre-dried nano-silica and 2.5% by mass of 3-(trihydroxysilyl)propanesulfonic acid are dispersed in an ethanol aqueous solution with a mass ratio of 1:1. The mixture is refluxed at 75°C, and after centrifugation, washing and drying, sulfonated nano-silica is obtained. S102. The sulfonated nano-silica obtained in step S101 is dispersed in a mixed solution containing calcium salt, magnesium salt and aluminum salt, the pH is adjusted to 10-11, and a co-precipitation reaction is carried out at 70℃ for 9 h to allow calcium magnesium aluminum layered bimetallic hydroxide nanosheets to grow in situ on the surface of nano-silica. After centrifugation, washing and drying, silicon-based hydrotalcite material is obtained. S2. Preparation of the pre-dispersion: Weigh water according to the ratio, add silicon-based hydrotalcite material and polyethylene glycol to water, and ultrasonically disperse at 400W ultrasonic power and 45kHz frequency for 15 minutes to obtain a pre-dispersion. S3. Preparation of dry powder mixture: Weigh out ordinary silicate cement, rapid-hardening sulfoaluminate cement, anhydrous gypsum, silane-modified calcium oxide, and additives according to the proportions, put them into a dry powder mixer, and stir and mix them at 25 rpm for 10 minutes to obtain a dry powder mixture. S4. Preparation of grouting material: Pour the pre-dispersed liquid into a planetary high-speed pulper with a stirring blade linear velocity ≥10m / s and stir at a low speed of 400rpm. While stirring, slowly add the dry powder mixture, and complete the addition within 45s. After all the dry powder has been added, increase the stirring speed to 1300rpm and stir at high speed for 2min. Then reduce the stirring speed to 500rpm and let it stand for 10min. Finally, stir at 900rpm for 45s to obtain the prestressed duct grout.
[0023] Example 3: Preparation of prestressed duct grouting material: The prestressed duct grouting material comprises the following components in parts by weight:
[0024] S1. Preparation of multifunctional nano-silica: S101. Pre-dried nano-silica and 2.5% by mass of 3-(trihydroxysilyl)propanesulfonic acid are dispersed in an ethanol aqueous solution with a mass ratio of 1:1. The mixture is refluxed at 75°C, and after centrifugation, washing and drying, sulfonated nano-silica is obtained. S102. The sulfonated nano-silica obtained in step S101 is dispersed in a mixed solution containing calcium salt, magnesium salt and aluminum salt, the pH is adjusted to 10-11, and a co-precipitation reaction is carried out at 70℃ for 9 h to allow calcium magnesium aluminum layered bimetallic hydroxide nanosheets to grow in situ on the surface of nano-silica. After centrifugation, washing and drying, silicon-based hydrotalcite material is obtained. S2. Preparation of the pre-dispersion: Weigh water according to the ratio, add silicon-based hydrotalcite material and polyethylene glycol to water, and ultrasonically disperse at 400W ultrasonic power and 45kHz frequency for 15 minutes to obtain a pre-dispersion. S3. Preparation of dry powder mixture: Weigh out ordinary silicate cement, rapid-hardening sulfoaluminate cement, anhydrous gypsum, silane-modified calcium oxide, and additives according to the proportions, put them into a dry powder mixer, and stir and mix them at 25 rpm for 10 minutes to obtain a dry powder mixture. S4. Preparation of grouting material: Pour the pre-dispersed liquid into a planetary high-speed pulper with a stirring blade linear velocity ≥10m / s and stir at a low speed of 400rpm. While stirring, slowly add the dry powder mixture, and complete the addition within 45s. After all the dry powder has been added, increase the stirring speed to 1300rpm and stir at high speed for 2min. Then reduce the stirring speed to 500rpm and let it stand for 10min. Finally, stir at 900rpm for 45s to obtain the prestressed duct grout.
[0025] Comparative Example 1: Compared with Example 3, in Comparative Example 1, the amount of ordinary silicate cement was 450 parts, the amount of rapid-hardening sulfoaluminate cement was 300 parts, and other conditions remained unchanged.
[0026] Comparative Example 2: Compared with Example 3, no silane-modified calcium oxide was added in Comparative Example 2, while other conditions remained unchanged.
[0027] Comparative Example 3: Compared with Example 3, in Comparative Example 3, unmodified ordinary calcium oxide was used instead of silane-modified calcium oxide, while other conditions remained unchanged.
[0028] Comparative Example 4: Compared with Example 3, no polyethylene glycol was added in Comparative Example 4, while other conditions remained unchanged.
[0029] Comparative Example 5: Compared with Example 3, in Comparative Example 5, polycarboxylate high-performance water-reducing agent (powder) was used instead of naphthalene-based high-efficiency water-reducing agent, while other conditions remained unchanged.
[0030] Performance testing: 1. According to JTG / T 3650-2020 "Technical Specifications for Construction of Highway Bridges and Culverts" and relevant national standards, the following performance tests are required for this grouting material: Flowability testing shall be conducted according to Appendix A.2 of JTG / T 3650-2020 using the flow cone method, measuring the initial flowability and the flowability after 30 minutes of mixing; Bleeding rate and pressure bleeding rate testing shall be conducted according to Appendix A.6 and Appendix A.7 of JTG / T 3650-2020, measuring the 3-hour free bleeding rate, the 3-hour inter-wire bleeding rate, the 24-hour free bleeding rate, and the pressure bleeding rate; In the expansion rate test, the 3-hour free expansion rate shall be measured according to Appendix A.4 of JTG / T 3650-2020 using the graduated cylinder method, and the 7-day restricted expansion rate shall be measured according to Appendix A.5; Setting time shall be measured according to GB / T 1346-2024 "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement"; Compressive strength shall be measured according to GB / T The strength of cement mortar was determined according to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)"; the total chloride ion content was determined according to Appendix B of JG / T313-2014 by potentiometric titration; and the sulfur trioxide content was determined according to GB / T 176-2017 "Chemical Analysis Methods for Cement".
[0031] 2. Chloride ion adsorption test of hardened grout Test steps: (1) The grouting material prepared according to the present invention is molded into 40mm×40mm×40mm test blocks, and after standard curing for 28 days, it is crushed, ground, and passed through a 0.63mm sieve. The powder under the sieve is then vacuum dried at 60℃ to constant weight. (2) Accurately weigh 1.000g of powder and place it in a centrifuge tube. Add 50mL of 0.1mol / L NaCl solution and shake at 150 r / min for 24h in a constant temperature shaker at 25±1℃. (3) After shaking, centrifuge at 8000 r / min for 10 min, take the supernatant and determine the concentration of residual chloride ions by silver nitrate titration (Mohr's method).
[0032] Calculation formula: Chloride ion adsorption rate: η = (C0 - C e ) / C0×100%, where C0 is the initial chloride ion concentration, C e To balance the chloride ion concentration.
[0033] The mixing ratios of the above embodiments and comparative examples are summarized below:
[0034] The performance tests were conducted on the embodiments and comparative examples as described above, and the data obtained are shown in Tables 1, 2 and 3.
[0035] Table 1. Flowability and bleeding performance data of each embodiment and comparative example.
[0036] 1. Flowability data analysis As can be seen from the data in Table 1, the initial flowability of Examples 1, 2, and 3, and Comparative Examples 1 and 2, were all within the range of 15.5-17.0 s, and the flowability at 30 min remained within the range of 18.0-20.0 s, with minimal flowability loss over time. All met the requirements of JTG / T 3650-2020 (initial flowability 14-18 s, 30 min flowability ≤ 22 s). Example 3 showed the best performance, with an initial flowability of 15.5 s and a flowability at 30 min increasing only to 18.0 s, resulting in a flowability loss of only 2.5 s over time.
[0037] Comparative Example 3 used unmodified ordinary calcium oxide instead of silane-modified calcium oxide. The initial fluidity increased to 22.0 s, and after 30 minutes, the fluidity surged to 28.0 s, with a fluidity loss of 6.0 s, and both indicators exceeded the standard. This is because ordinary calcium oxide immediately hydrates and releases heat upon adding water, releasing a large amount of Ca. 2+ It interacts electrostatically with the sulfonate group of the high-efficiency naphthalene-based water-reducing agent, weakening the dispersion effect of the water-reducing agent; at the same time, the hydration of calcium oxide consumes free water, resulting in a decrease in the actual water-cement ratio of the slurry and a decrease in fluidity.
[0038] Comparative Example 4, without the addition of polyethylene glycol, had an initial flowability of 15.0 s (slightly better than Example 3) and a flowability of 17.5 s after 30 min, showing good flowability retention. This indicates that the flowability was slightly improved without the addition of polyethylene glycol, because polyethylene glycol has a certain thickening effect and will slightly increase the viscosity of the slurry.
[0039] Comparative Example 5 used a polycarboxylate superplasticizer instead of a high-efficiency naphthalene-based superplasticizer. The initial flowability was 18.5 s, and the 30-minute flowability was 25.0 s, both significantly worse than those of Example 3. This is because the carboxyl functional groups of the polycarboxylate superplasticizer react with the Ca released during the hydrolysis of calcium oxide. 2+ A complexation reaction occurs, forming an insoluble calcium carboxylate precipitate, which leads to the water-reducing agent being consumed in large quantities and becoming ineffective.
[0040] 2. Analysis of water seepage performance data The bleeding performance is examined from the following four perspectives: free bleeding is the most basic requirement, bleeding between steel wires is closer to the actual working conditions, 24-hour bleeding examines long-term stability, and pressure bleeding tests the ability to resist bleeding under construction and service pressure. The bleeding resistance of the grout is evaluated from different perspectives.
[0041] Bleeding in grouting refers to the phenomenon where free water rises and separates from the grout during the settling process. Bleeding is mainly related to the water-cement ratio, water-retaining components, water-reducing agents, total amount of cementitious materials, characteristics of expanding agents, and mixing uniformity: the higher the water-cement ratio and the more free water, the easier it is to bleed; water-retaining materials such as polyethylene glycol and silicone-based hydrotalcite can bind water and reduce bleeding; excessive water-reducing agents can cause excessive particle dispersion and aggravate bleeding; sufficient cementitious materials can form a dense skeleton and restrict water migration; early-expansion expanding agents can squeeze water during the plastic stage of the grout, leading to increased bleeding; uneven mixing can easily create localized water-rich areas, causing bleeding.
[0042] The bleeding rate of Examples 1, 2, 3 and Comparative Examples 1 and 2 was 0%, the bleeding rate between steel wires was 0% after 3 hours, the free bleeding rate was 0% after 24 hours, and the pressure bleeding rate was ≤0.3%, all of which met the specifications.
[0043] Comparative Example 3 (ordinary calcium oxide) showed significant water bleeding: the free water bleeding rate was 1.2% after 3 hours, and the pressure water bleeding rate was 1.5%. This is because ordinary calcium oxide undergoes vigorous hydration in the early stages, and the localized heat release leads to an increase in the temperature of the slurry, which accelerates the settling rate of cement particles. At the same time, the remaining water after hydration consumes free water is more easily discharged.
[0044] Figure 1 The graph shows the water seepage performance data of the embodiments and comparative examples of the present invention. It can be seen from the graph that the water seepage of Comparative Example 4 (without polyethylene glycol) is the most severe: the free water seepage rate is as high as 2.5% after 3 hours, the water seepage rate between the steel wires is 1.8% after 3 hours, the free water seepage rate is 1.2% after 24 hours, and the pressure water seepage rate is 2.0%. This indicates that polyethylene glycol is the key component for inhibiting water seepage.
[0045] Comparative Example 5 (polycarboxylate superplasticizer) showed slight bleeding: 0.5% free bleeding rate after 3 hours and 0.8% pressure bleeding rate. This is because the polycarboxylate superplasticizer has strong air-entraining properties. After the bubbles collapse, they form interconnected pores, which become channels for moisture migration, thus causing bleeding.
[0046] Table 2. Expansion performance and condensation time data for each embodiment and comparative example.
[0047] The following patterns can be observed from the expansion performance and condensation time data in Table 2: Regarding expansion performance, the 3-hour free expansion rates of Examples 1, 2, and 3, and Comparative Examples 1, 4, and 5 were all stable between 0.5% and 0.6%, and the 7-day restricted expansion rates were between 0.03% and 0.04%. The onset time of exothermic hydration of calcium oxide was approximately 3 hours, fully meeting the specifications. This indicates that the silane-modified calcium oxide designed in this invention can effectively achieve delayed expansion, maintaining plasticity and not expanding initially after water addition, and exhibiting stable micro-expansion after the slurry initially sets (approximately 4.5 hours).
[0048] Of particular note is Comparative Example 2, which did not add any form of calcium oxide expansive agent. Its 3-hour free expansion rate was only 0.2%, significantly lower than the groups with added expansive agents. More importantly, its 7-day restricted expansion rate showed a negative value (i.e., shrinkage). This shrinkage phenomenon occurs because cement-based materials inevitably undergo chemical shrinkage (the solid volume of cement hydration products is smaller than the original volume of the reactants, resulting in chemical shrinkage) and drying shrinkage (the evaporation of internal free water leads to volume reduction). When no expansive agent provides compensation, these shrinkage effects manifest as a decrease in the net volume of the specimen. Specifically, at 7 days, cement hydration has entered a deceleration phase, and the cumulative effect of chemical shrinkage is significant. Meanwhile, the internal free water of the paste is gradually consumed, and capillary tension increases, both contributing to volume shrinkage. The 7-day restricted expansion rate of Comparative Example 2 was -0.01%. Although the value is small, it indicates that the system cannot compensate for shrinkage on its own. In the long term, this may lead to incomplete pore filling, prestress loss, and even an increased risk of steel reinforcement corrosion. In contrast, all groups with added silane-modified calcium oxide achieved micro-expansion, demonstrating the necessity of the delayed expansion technology in this scheme.
[0049] Comparative Example 3 used unmodified ordinary calcium oxide instead of silane-modified calcium oxide. Its 3-hour free expansion rate reached 1.5%, far exceeding the upper limit of the specification, and the 7-day restricted expansion rate also reached 0.15%. The onset time of calcium oxide hydration exothermic reaction was only 0.5 hours. This is because ordinary calcium oxide lacks a hydrophobic protective layer. After adding water, it immediately reacts with water to form calcium hydroxide, resulting in a rapid expansion in volume and a concentrated release of hydration heat. This premature and rapid expansion not only fails to effectively compensate for later shrinkage but also damages the cement stone structure that has not yet formed strength during the plastic stage of the slurry, leading to poor volume stability. At the same time, the fluidity will also decrease rapidly due to early hydration. The early expansion will squeeze water during the plastic stage of the slurry, resulting in increased bleeding, which is consistent with the bleeding situation in Table 1.
[0050] Regarding setting time, Examples 1, 2, and 3 had an initial setting time of 4.5 hours and a final setting time of 8.5 hours, meeting the specifications and providing sufficient construction operation window. Comparative Example 1, due to its relatively high proportion of rapid-hardening sulfoaluminate cement, showed slightly faster setting (initial setting 4 hours, final setting 7.5 hours). Comparative Example 2 lacked calcium oxide expanding agent, thus lacking the promoting effect of calcium oxide hydration heat and Ca... 2+ The accelerating effect of calcium oxide significantly accelerated the cement hydration process, extending the setting time to 5 hours for initial setting and 10 hours for final setting. In Comparative Example 3, the intense early hydration and exothermic reaction of ordinary calcium oxide significantly accelerated the cement hydration process, resulting in a markedly shorter setting time (3.5 hours for initial setting and 6.5 hours for final setting). Comparative Example 5, using polycarboxylate superplasticizer, exhibited a strong dispersing effect on cement particles, which delayed the hydration reaction, extending the setting time to 5 hours for initial setting and 9.5 hours for final setting.
[0051] Table 3 Chloride ion-related properties and compressive strength data for each embodiment and comparative example.
[0052] The following patterns can be observed from the chloride ion-related properties and compressive strength data in Table 3: Regarding compressive strength, the 7-day and 28-day compressive strengths of Examples 1, 2, and 3 increased with increasing dosage within the range of 3-5.5 parts of silicon-based hydrotalcite, with Example 3 showing the best performance. When the dosage was further increased to 8 parts, the strength decreased slightly, indicating that excessive addition would have a slight negative impact on strength. This is because the nano-silica cores in the silicon-based hydrotalcite have a filling effect, which can refine the pores of the cement paste. At the same time, the hydrotalcite component in the LDH shell can participate in cement hydration and synergistically interact with the cement hydration products to jointly improve the density and strength of the paste. Figure 2 The figure shows a physical image of the standard curing test block of the grouting material prepared in Example 3 of the present invention. As can be seen from the figure, the test block has a regular overall shape, complete edges and corners, and a dense and uniform surface without obvious cracks, honeycomb holes and delamination defects. The grout hardening and molding effect is excellent, which meets the requirements of engineering grouting density and structural molding.
[0053] Comparative Example 1, due to its low content of ordinary silicate cement, resulted in a slight decrease in the total amount of cementitious materials and a slight decrease in strength. Comparative Example 2, lacking the addition of silane-modified calcium oxide, lacked the activating effect of calcium hydroxide produced by calcium oxide hydration on cement hydration, and also lacked the hydration heat-promoting effect, resulting in a significant decrease in strength. Comparative Example 3, using ordinary calcium oxide, while accelerating early strength development through intense early hydration exotherm, led to uneven distribution of hydration products due to the rapid reaction, and early expansion may have caused microcracks, ultimately resulting in a lower 28-day strength than Example 3. Comparative Example 4, lacking polyethylene glycol, exhibited bleeding in the slurry, leading to localized uneven water-cement ratios, increased porosity after hardening, and a slight decrease in strength. Comparative Example 5, using polycarboxylate superplasticizer, while exhibiting good dispersion, suffered significant fluidity loss over time, and the complexation reaction with calcium ions consumed some of the superplasticizer, resulting in decreased slurry uniformity and a lower strength than Example 3.
[0054] Regarding the total chloride ion content, the total chloride ion content in all examples and comparative examples was 0.008%-0.009%, which is far below the limit of 0.02% required by the specification. This proves that the present solution effectively controls the introduction of chloride ions in the selection of raw materials and the production process, and poses no risk of corrosion to the prestressed tendons.
[0055] Regarding chloride ion adsorption rate, Example 1, with its low silicon-based hydrotalcite content, achieved an adsorption rate of 20.2%; Example 3, with a moderate content, achieved an adsorption rate of 22.5%; and Example 2, with the highest content, achieved an adsorption rate of 24%, showing a clear positive correlation between content and adsorption rate. All comparative examples contained the same amount (5.5 parts) of silicon-based hydrotalcite material, and their adsorption rates were close to those of Example 3, approximately 22%. This fully demonstrates that silicon-based hydrotalcite material is the core component for chloride ion adsorption. Its interlayer nitrate ions can actively capture externally diffused chloride ions through an ion exchange mechanism, fixing them within the interlayer, thereby reducing the concentration of free chloride ions in the pores and delaying the corrosion of the prestressing tendons.
[0056] Regarding sulfur trioxide content, the sulfur trioxide content in all examples and comparative examples was between 5.9% and 6.1%, far below the standard limit of 12%. This content is due to the introduction of anhydrous gypsum (the main component of which is calcium sulfate). An appropriate amount of sulfur trioxide helps to react with the aluminate phase to form ettringite, which regulates the setting time and expansion performance, and does not pose a risk of corrosion to the reinforcing steel.
[0057] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A prestressed duct grouting material, characterized in that, Composed of the following components by mass: 450-550 parts of ordinary Portland cement; 250-350 parts of rapid-hardening sulfoaluminate cement; 40-70 parts anhydrous gypsum; 20-40 parts of silane-modified calcium oxide; 3-8 parts of silicon-based hydrotalcite material; 0.5-2 parts of polyethylene glycol; 5-9 parts of admixture; 260-300 parts water; The number-average molecular weight of the polyethylene glycol is 1000-3000 Da; The admixture is a compound of a high-efficiency naphthalene-based water-reducing agent and sodium citrate in a mass ratio of 20-40:1; The silicon-based hydrotalcite material is a calcium magnesium aluminum layered bimetallic hydroxide@nano silica core-shell material, wherein the nano silica is the core, and the calcium magnesium aluminum layered bimetallic hydroxide nanosheets are grown in situ on the surface of the nano silica to form a shell layer, which has the function of chloride ion adsorption, with a chloride ion adsorption rate ≥20%.
2. The prestressed duct grouting material according to claim 1, characterized in that, The anhydrous gypsum has a specific surface area of 300-500 m². 2 / kg.
3. The prestressed duct grouting material according to claim 1, characterized in that, The silane-modified calcium oxide is prepared by the following steps: Octyltriethoxysilane or dodecyltrimethoxysilane is pre-hydrolyzed and then sprayed into calcium oxide powder. The mixture is stirred at 80°C for 30 minutes and dried to obtain silane-modified calcium oxide. The amount of silane used is 2%-5% of the mass of calcium oxide. The modified calcium oxide is stable in dry powder form and begins to hydrate and release heat 2-4 hours after adding water. The total expansion rate is 0.02%-0.05%.
4. The prestressed duct grouting material according to claim 1, characterized in that, In the preparation steps of the silicon-based hydrotalcite material: S1. Disperse pre-dried nano-silica in a mixed solvent of ethanol and deionized water in a volume ratio of 1:1, add 1.5%-3.5% of 3-(trihydroxysilyl)propanesulfonic acid by mass of nano-silica, reflux at 70-80℃ for 3-6 hours, centrifuge, wash and dry to obtain sulfonated nano-silica. S2. The sulfonated nano-silica obtained in step S1 is dispersed in a mixed solution containing calcium salt, magnesium salt and aluminum salt. The pH is adjusted to 10-11, and a co-precipitation reaction is carried out at 60-80℃ for 6-12 h to allow calcium-magnesium-aluminum layered bimetallic hydroxide nanosheets to grow in situ on the surface of nano-silica. After centrifugation, washing and drying, silicon-based hydrotalcite material is obtained. The calcium salt is calcium nitrate, the magnesium salt is magnesium nitrate, and the aluminum salt is aluminum nitrate. The molar ratio of calcium, magnesium and aluminum is 2-4:1:1, and the interlayer anion is nitrate.
5. A method for preparing the prestressed duct grouting material according to any one of claims 1 to 4, characterized in that, Includes the following steps: T1. Preparation of pre-dispersion: Weigh water according to the ratio, add silicon-based hydrotalcite material and polyethylene glycol to water, and ultrasonically disperse at 300-500W ultrasonic power and 40-50kHz frequency for 10-20 minutes to obtain a pre-dispersion. T2. Preparation of dry powder mixture: Weigh out ordinary silicate cement, rapid-hardening sulfoaluminate cement, anhydrous gypsum, silane-modified calcium oxide, and additives according to the proportions, put them into a dry powder mixer, and stir and mix them at a speed of 20-30 rpm for 10-15 minutes to obtain a dry powder mixture. T3. Preparation of grouting material: Pour the pre-dispersed liquid into a high-speed pulping machine, start the agitator and stir at a low speed of 300-500 rpm, while slowly adding the dry powder mixture, and complete the addition within 30-60 seconds; after all the dry powder has been added, increase the stirring speed to 1200-1500 rpm and stir at high speed for 2-3 minutes; then reduce the stirring speed to 400-600 rpm and let it stand for 5-10 minutes; finally, stir at 800-1000 rpm for 30-60 seconds to obtain the prestressed duct grouting material.
6. The method for preparing a prestressed duct grouting material according to claim 5, characterized in that, The high-speed pulper described in T3 is a planetary high-speed pulper with a stirring blade linear velocity ≥10m / s.
7. The method for preparing a prestressed duct grouting material according to claim 5, characterized in that, The performance indicators of the grouting material are as follows: initial fluidity 14-18s, 30min fluidity ≤22s, 3h bleeding rate 0%, 3h free expansion rate 0-2%, 7d compressive strength ≥50MPa, and 28d compressive strength ≥60MPa.
Citation Information
Patent Citations
High-durability micro-expansion green prestressed duct grouting material and preparation method thereof
CN113061002A
Sulphoaluminate cement-based negative temperature pressure slurry and preparation method thereof
CN117735942A
Negative-temperature prestressed duct grouting material and preparation method thereof
CN117800689A